The Impact Of Incentives On Functionality Performance A Case Study Of El Oued University - Tir Abdelhak (جامعة الوادي University Of Eloued, 2024)
The study aims to measure the effect of (incentives) on (functionality performance)- case study of El-oued University in Algeria. Our study relies on a model that measures the impact of each of the financial, moral, and social incentives on functionality performance in the institution. The descriptive method was used to describe the variables of the study, and the inductive approach to judge the whole through the part. The data and the information were collected through the questionnaire form in a number of 150 forms. We use also the SPSS statistical program to estimate the standard model. The study reached a conclusion that incentives of all kinds have a positive effect on functionality performance of EL-OUED University.
Keywords: Incentives; financial incentives; moral incentives; social incentives; functionality performance